Authentication of Barbonymus spp. From Lake Singkarak Using DNA Barcoding: Authentication of Barbonymus spp. From Lake Singkarak using DNA Barcoding - Salis, Viola Mutiara; Roesma, Dewi Imelda; Tjong, Djong Hon; Syaifullah; Aadrean; Dahelmi (Journal of Tropical Life Science, 2024)
The local community distinguishes between Barbonymus belinka (Balingka) and Barbonymus schwanefeldii (Kapiek) in Lake Singkarak based on size due to the morphological similarities between the two species. From previous reports, B. belinka (Balingka) is a fish endemic to Lake Singkarak, West Sumatra, while B. schwanefeldii has a wider distribution, including Sumatra, Kalimantan, and Java. Consequently, molecular identification is necessary to discern between the species and to understand the DNA barcode characteristics of fish belonging to the genus Barbonymus in Lake Singkarak. One molecular technique utilized for species identification is DNA barcoding, which focuses on the COI (Cytochrome Oxidase Subunit I) gene. Liver tissue samples from Balingka and Kapiek fish from Lake Singkarak were used in the study. Based on 585 bp of COI gene sequences and 30 comparison sequences from BOLD system and GenBank NCBI, seven samples from Lake Singkarak show a genetic distance of 0–1.2% from B. schwanefeldii populations elsewhere, with 15 differing nucleotide bases. Moreover, samples from Lake Singkarak show a genetic distance of 7.7–8.2% from B. belinka in the BOLD system from Aceh, with 42 differing nucleotide bases. Furthermore, two specific bases are present in B. schwanefeldii from Lake Singkarak. Based on the results of this research, it is known that all samples from Lake Singkarak, including Balingka and Kapiek, belong to the same species, namely B. schwanefeldii.